PENANGANAN PEMBIAYAAN MURABAHAH BERMASALAH DI BPRS AL FALAH BANYUASIN PADA MASA PANDEMI COVID-19 - Iska Sanjaya; Meriyati Meriyati; Choirunnisak Choirunnisak (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
This study aims to determine (1) the inhibiting factors that affect the financing of problematic murabahah found at BPRS Al Falah Banyuasin during the covid-19 pandemic. (2) Handling problematic murabahah financing carried out at BPRS Al Falah Banyuasin during the covid-19 pandemic. This study uses a qualitative research type. This research is descriptive research. The population in this study were several employees and customers of BPRS Al Falah Banyuasin. The data analysis technique in this study uses a way of analyzing and assessing all relevant data and facts obtained from the selected object and quoting from generally accepted theories and provisions then from the results of the analysis the author tries to draw conclusions that represent the existing problems. The results of this study the authors conclude that: (1) The obstacles in murabahah financing at BPRS Al Falah Banyuasin are the ability to pay from customers, global economic conditions, human resources, customer character, completeness of documents or administration, and customer delays in paying installments. (2) Handling murabahah financing at BPRS Al Falah Banyuasin, namely billing on the principle of kinship, giving warnings or reprimands, rescheduling (Rescheduling), reconditioning, restructuring.